Culturally appropriate, effective provision for Māori learners with special needs : he waka tino whakarawea : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Education at Massey University, Palmerston North, Aotearoa/New Zealand - Bevan-Brown, Jill (Massey University, 2002)
How can Māori learners with special needs have their needs met in a culturally appropriate, effective way? What challenges exist and how can they be met? A multi-method approach was used to answer these questions. This involved a review of Aotearoa/New Zealand and international literature; a written survey of 78 people from 56 special education, Māori and disability organisations; interviews with 25 organisation personnel, 38 parents and whānau and four Māori learners with special needs; a six year case study of one learner; and four consultation meetings with 50 people from six kōhanga reo. To assist in evaluating the cultural effectiveness of programmes and services, a cultural audit checklist and process were developed and trialed in 11 educational establishments. Feedback on the cultural audit was also obtained from the kōhanga reo focus groups. Research data revealed that despite recent improvements, Māori learners with special needs are not being adequately provided for. Major challenges are a widespread shortage of culturally appropriate resources, services, programmes and people with the necessary cultural, language and professional expertise and the existence of beliefs and attitudes detrimental to Māori learners with special needs. Recommendations to meet these challenges include a substantial increase in funding to overcome identified shortages; the establishment of compulsory bicultural training for all relevant occupation groups; and the introduction of proactive measures to enable Māori to enter special education-related occupations. The research data also revealed that programmes and services should be based on Māori perspectives of special needs and incorporate Māori concepts, knowledge, skills, attitudes, language, practices, customs, values and beliefs; focus on areas of importance, concern and benefit to Māori; involve and empower parents, whānau, the Māori community and the learners themselves; be of a high quality; accessible; result in equitable outcomes for Māori learners; and be delivered by people with the required personal, professional and cultural expertise. The cultural audit was seen as an effective means of helping educational establishments evaluate and improve their programmes and services for Māori learners with special needs. However, findings also indicated that for long-term, widespread improvement to be achieved, genuine power sharing and societal-level changes in the ideologies, systems and circumstances that disadvantage Māori are needed.
Keywords: Māori (New Zealand people); Special education; New Zealand; Children with disabilities; Hauātanga; Hōtaka (Ako); Mātauranga; Rauemi; Māori Doctoral Thesis; Fields of Research::330000 Education::330100 Education Studies::330108 Special education